To Investigate the Foreign Investment in US Stock Market in Overcoming the Rising Inflation Rate in Malaysia - Wee Win Yeoh (West Science Journal Economic and Entrepreneurship, 2023)
The purpose of this study had been targeted to explore the investigation on the foreign investment in US stock market in aligned to understand the potential market return to overcome the rising inflation rate in Malaysia. This had been motivated by the increasing interest and preference among the local investors in Malaysia into seeking into alterative investment method in foreign investment market which include foreign stock market. Therefore, the quantitative study had been conducted where the combination of the correlation analysis and regression analysis will test the research framework for the study and further comparative analysis had bene used to identify the comparison between the performance of the foreign stock market return against the inflation rate in Malaysia. The results had proven that only the inflation rate between Malaysia and US remained significant having positive relationship between the two variables rejecting other suggestion from the research framework. The comparative analysis had unveiled that the foreign stock market return considering the exchange rate through NYSE and NASDAQ had been greater and significantly surpass the inflation rate in Malaysia suggesting the recommendation for the investors to invest in the US stock market to overcome the inflation pressure in Malaysia.